Are Illness Perceptions Associated With Disease Activity or Psychological Well-Being in Rheumatoid Arthritis? A Study With the Evidence of Confirmatory Factor Analysis - Yasemin ULUS; Berna TANDER; Yeşim AKYOL; Yüksel TERZİ and Yeliz ZAHİROĞLU and Gökhan SARISOY and Ayhan BİLGİCİ and Ömer KURU (Archives of Rheumatology, 2017)
Objectives: This study aims to assess the factor structure of the Turkish Revised Illness Perception Questionnaire (IPQ-R) in patients with rheumatoid arthritis (RA) and the relationship of illness perceptions with disease activity and psychological well-being. Patients and methods: One hundred and fifty RA patients (8 males, 142 females; mean age 51.1±12.7 years; range 21 to 81 years) were included in the study. Confirmatory factor analysis was used to test the factor structure of the IPQ-R. Pain was assessed by visual analog scale, disease activity by Disease Activity Score 28, depression by Beck Depression Inventory, global life satisfaction by the Satisfaction with Life Scale, and illness perception by the IPQ-R. Results: Three items (items 12, 18, 19) were deleted because of poor factor loadings. The modified 35-item model showed good reliability and discriminant validity. Beck Depression Inventory scores were correlated with identity, consequences, and emotional representations subscales positively (p<0.001); and with illness coherence subscale negatively (p<0.05). There were positive correlations between Satisfaction with Life Scale scores, and treatment control and illness coherence subscales (p<0.05). Satisfaction with Life Scale scores were negatively correlated with identity, emotional representation, and timeline acute/chronic subscales (p<0.05), and consequences subscale (p<0.001). Disease Activity Score 28 was not correlated with IPQ-R domains (p>0.05). Conclusion: The Turkish IPQ-R appears to be a useful clinical assessment tool to evaluate RA-related illness perceptions. RA healthcare should include psychological intervention to strengthen patients’ beliefs about their RA regardless of disease activity.